Unmanned combat concept based on DoDAF research on systematic description method - LI Yuhao, DU Bo, LIU Yuanyi (Zhihui kongzhi yu fangzhen)
In response to the unclear explanation of the constituent elements and mapping relationships in the description of unmanned combat concepts, as well as the lack of structured and systematic description theory methods, a systematic description method for unmanned combat concepts based on the Department of Defense Architecture Framework (DoDAF) is proposed, which systematically explains the constituent elements of unmanned combat concept and the mapping relationships between constituent elements, building a conceptual architecture framework for unmanned combat targeting a certain capture and control operation relies on this method. The decomposition modeling method based on typical elements provide reference for the development and deduction verification of combat concepts, mining of combat capability requirements, and design of combat systems.